MEET. An interactive exhibition itinerary between co-design and enhancement of the territory - Silvia Gasparotto; Alessandra Bosco; Margo Lengua; Pietro Baruzzi (Agathón)
In a context of socio-economic and cultural transformations, the diffusion of digital technologies has played a significant role by providing a horizontal tool that can stimulate sharing, simplify communication, and support the physical experience of a place. Even museums and exhibition itineraries, combining physical and digital dimensions, become places of hybridisation. This paper presents a research programme that investigates the field of design for Cultural Heritage. MEET (Multifaceted Experiences for Enhancing Territories) is a collaborative project format that involves institutions, professionals, and citizens in the realisation of an interactive exhibition itinerary dedicated to the enhancement of the local Cultural Heritage through co-design processes.